1997
DOI: 10.1021/bi961542p
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Synthesis, Structural Modeling, and Biological Activity of the Epidermal Growth Factor-like Domain of HumanCripto

Abstract: Cripto, also known as human teratocarcinoma-derived growth factor 1 (TDGF-1), contains a 40 amino acid region with some similarity to the epidermal growth factor (EGF) domain. However, sequence homology is largely restricted to the classical cysteine/glycine motif with only limited similarities in other regions. Significant differences to human EGF include the absence of all seven residues between the two N-terminal half-cystines and a five-residue shorter loop between the third and fourth half-cystines. We ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 42 publications
0
30
0
Order By: Relevance
“…However, recombinant CR-1 in radioreceptor competition assays with 125 I-EGF in human mammary MCF-10A cells or A431 epidermoid carcinoma cells failed to demonstrate any binding to the EGFR on these cells (Kannan et al 1997). Reciprocally, 125 I-CR-1 binding to several different human breast carcinoma cells lines could be blocked by CR-1 but not by EGF, TGFα, BTC, AR or HRGβ1.…”
Section: Transactivation Of Erb B-4 and Fgfr-1 By Cr-1mentioning
confidence: 92%
See 3 more Smart Citations
“…However, recombinant CR-1 in radioreceptor competition assays with 125 I-EGF in human mammary MCF-10A cells or A431 epidermoid carcinoma cells failed to demonstrate any binding to the EGFR on these cells (Kannan et al 1997). Reciprocally, 125 I-CR-1 binding to several different human breast carcinoma cells lines could be blocked by CR-1 but not by EGF, TGFα, BTC, AR or HRGβ1.…”
Section: Transactivation Of Erb B-4 and Fgfr-1 By Cr-1mentioning
confidence: 92%
“…Reciprocally, 125 I-CR-1 binding to several different human breast carcinoma cells lines could be blocked by CR-1 but not by EGF, TGFα, BTC, AR or HRGβ1. Finally, recombinant CR-1 using BAF/3 mouse lymphoid cells that were ectopically expressing the human EGFR, erb B-2, erb B-3, or erb B-4 either alone or in various pairwise combinations was unable to activate directly the tyrosine phosphorylation of these tyrosine kinase receptors, demonstrating that CR-1 was not able to bind directly to these type 1 receptor kinases either as homodimers or as heterodimers (Kannan et al 1997).…”
Section: Transactivation Of Erb B-4 and Fgfr-1 By Cr-1mentioning
confidence: 99%
See 2 more Smart Citations
“…Transfection of human Cripto results in transformation of and NOG-8 mouse normal mammary epithelial cells [8]. Experiments using the refolded CRIPTO peptide have shown that CRIPTO can induce tyrosine phosphrylation of the SH2 adapter protein She in HC-11 cells, resulting in increased association of She with Grb2 and elevated MAPK kinase activity [2,9]. More recently it has been shown that recombinant CRIPTO can transactivate erbB-A receptor, but not EGF receptor, erbB-2 and erbB-3 [10].…”
Section: Introduction 51 Background and Significancementioning
confidence: 99%